2015
DOI: 10.1177/0734016815573308
|View full text |Cite
|
Sign up to set email alerts
|

Media, Gender, and Fear of Crime

Abstract: Few studies have examined how the intersection of gender and race/ethnicity may manifest differences in the effects of crime-related media on fear of crime. This study examines the relationships between various forms of crime-related media on fear of crime with a sample disaggregated by gender to ascertain if crime-related media consumption works differently for women and men. Race/ethnic differences within gender were also examined. Only slight differences between men and women were found and differences acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(24 citation statements)
references
References 68 publications
1
23
0
Order By: Relevance
“…Criminological studies have documented how crime news can intensify fear and public anxiety. 30 Although such media effects were important during the TV era, the current social-media era has changed the ways in which information is distributed. Although there is no doubt that more news and information are now accessible and can spread more rapidly than before, 31 researchers disagree as to whether social media has led to more diversified or segmented news consumption 32 and to the development of filter bubbles.…”
Section: Psychological Vulnerability and Cultivation Of Fear After Atmentioning
confidence: 99%
“…Criminological studies have documented how crime news can intensify fear and public anxiety. 30 Although such media effects were important during the TV era, the current social-media era has changed the ways in which information is distributed. Although there is no doubt that more news and information are now accessible and can spread more rapidly than before, 31 researchers disagree as to whether social media has led to more diversified or segmented news consumption 32 and to the development of filter bubbles.…”
Section: Psychological Vulnerability and Cultivation Of Fear After Atmentioning
confidence: 99%
“…Women report higher levels of fear despite the fact that men are significantly more likely to be violently victimized (Callan and Rosenberg 2015). However, gender differences in fear of crime might be due to the asymmetric risk of sexual victimization (Warr 1984), the typical picture of women as victims of crime (Callanan et al 2015) or that women tend to be "more sensitive to the consequences of victimization than men, and less able to control its occurrence" (Jackson 2009, p. 368). For example, women report higher levels of fear of sexual assault and other personal crimes (Henson et al 2013;Smolej et al 2006), but gender is not a statistically significant predictor in the fear of property crimes (Jackson 2009).…”
Section: Fear Of Crimementioning
confidence: 99%
“…While these studies continued to focus on television viewing, they looked at different types of television programming. Some studies found that watching local news produced more fear than watching national news (Callanan, 2012; Callanan & Rosenberger, 2015; Eschholz, Chiricos, & Gertz, 2003; Romer, Jamieson, & Aday, 2003; Weitzer & Kubrin, 2004). Other researchers reported that watching any type of news had no impact on fear of crime (Kort-Butler & Hartshorn, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other researchers reported that watching any type of news had no impact on fear of crime (Kort-Butler & Hartshorn, 2011). Fear also increased for those who watched crime dramas or reality television (Callanan, 2012; Callanan & Rosenberger, 2015; Eschholz et al, 2003; Kort-Butler & Hartshorn, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation